Internal Audit - Chambers, Andrew D.; Selim, Georges; Vinten, Gerald (London : Pitman publishing, 1987)
This book gave coverage to the practical concerns of auditors, auditees and directors.
includes index
Includes bibliographic references
ijb, 17/10/2018
Loans